2013
DOI: 10.1088/0031-8949/2013/t157/014049
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity studies of biopolymer electrolytes based on chitosan incorporated with NH4Br

Abstract: A polymer electrolyte system based on chitosan complexed with ammonium bromide (NH 4 Br) salt was prepared by the solution cast technique. 30 wt% NH 4 Br added electrolyte gave a room temperature conductivity of (4.38 ± 1.26) × 10 −7 S cm −1 and increased to (2.15 ± 0.47) × 10 −4 S cm −1 with addition of 40 wt% glycerol. The dependence of the conductivity on temperature proves that both chitosan-NH 4 Br and chitosan-NH 4 Br-glycerol systems are Arrhenian. The activation energy (E a) value for 70 wt% chitosan-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…For the unplastcized system, the highest conducting electrolyte with incorporation of 35 wt% NH 4 Br had the highest n and μ values of 3.64 × 10 18 cm −3 and 1.67 × 10 −4 cm 2 Table 4. Transport parameters of each electrolyte in plasticized system at room temperature [25]. It is known that blending two polymers can provide more complexation sites at which ion hopping and exchange can take place [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the unplastcized system, the highest conducting electrolyte with incorporation of 35 wt% NH 4 Br had the highest n and μ values of 3.64 × 10 18 cm −3 and 1.67 × 10 −4 cm 2 Table 4. Transport parameters of each electrolyte in plasticized system at room temperature [25]. It is known that blending two polymers can provide more complexation sites at which ion hopping and exchange can take place [21].…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity of starch-ammonium nitrate (NH 4 NO 3 ) increased from 2.83 × 10 −5 S cm −1 to 3.89 × 10 −5 S cm −1 by using a starch-chitosan blend [23,24]. From our previous works, the conductivity of chitosan-ammonium bromide (NH 4 Br) increased from (4.38 ± 1.26) × 10 −7 S cm −1 to (9.72 ± 0.95) × 10 −5 S cm −1 when using a starch-chitosan blend as the polymer host [25,26]. The blend of starch and chitosan was reported to form mechanically stable films due to the inter-and intramolecular hydrogen bonding that formed between the hydroxyl and amino groups of starch and chitosan [27].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of increasing the content of glycerol on the strength of the interaction between the components of the polymer blend is proved where additional ions are interacting with the oxygen atoms and nitrogen atoms [ 27 ]. The range of carboxamide and amine bands can be recognized straightforwardly as reported by Aziz et al [ 35 ] and Shukur et al [ 36 ]. Interestingly, a sharp peak lies between 901 and 1203 cm −1 that comes from the C-O stretching, which is in accordance with the findings of the study documented by Mejenom et al [ 37 ].…”
Section: Resultsmentioning
confidence: 77%
“…The shift shows the effect of glycerol concentration to provide more ions for the interaction with the oxygen and nitrogen atoms in the polymer blend [56]. Aziz et al [57] and Shukur et al [58] also reported a similar range of carboxamide and amine bands for their electrolyte systems. Lastly, the sharp peak located at (v) 900-1200 cm −1 possibly belongs to the C-O stretching which is comparable to the previous work reported by Mejenom et al [59] and Poy et al [60].…”
Section: Impedance Studymentioning
confidence: 85%